PKIB involved in the metastasis and survival of osteosarcoma - Wan, Rongxue; Yang, Gu; Liu, Qianzhen; Fu, Xiaokang; Liu, Zengping; Miao, Huilai; Liu, Huan; Huang, Wenhua (Frontiers in Oncology, 2022)
Osteosarcoma is frequently metastasized at the time of diagnosis in patients. However, the underlying mechanism of osteosarcoma metastasis remains poorly understood. In this study, we evaluated DNA methylation profiles combined with gene expression profiles of 21 metastatic and 64 non-metastatic osteosarcoma patients from TARGET database and identified PKIB and AIM2 as hub genes related to the metastasis of osteosarcoma. To verify the effects of PKIB on migration and invasion of osteosarcoma, we performed wound-healing assay and transwell assay. The results showed that PKIB significantly inhibited the migration and invasion of osteosarcoma cells and western blot experiments showed that the protein level of E-cad was up-regulated and VIM was down-regulated in 143-B cells recombinant expression PKIB. These results indicate that PKIB inhibit the metastasis of osteosarcoma. CCK-8 assay results showed that PKIB promote the proliferation of osteosarcoma. And the western blot results showed that the phosphorylation level of Akt was up-regulated in 143-B cells over-express PKIB, indicating that PKIB promotes the proliferation of osteosarcoma probably through signaling pathway that Akt involved in. These results give clues to us that PKIB was a potential target for osteosarcoma therapy. Furthermore, combined clinical profiles analysis showed that the expression of AIM2 and PKIB related risk scores was significantly related to the overall survival of osteosarcoma patients. Thus, we constructed a nomogram based on AIM2 and PKIB expression-related risk scores for osteosarcoma prognostic assessment to predict the 1-, 2-, 3- and 5-year overall survival rate of metastatic osteosarcoma patients, assisting clinicians in the diagnosis and treatment of metastatic osteosarcoma.